EVALUASI KINERJA CAMPURAN ASPAL DENGAN SUBTITUSI LIMBAH PLASTIK PET DALAM MENINGKATKAN DURABILITAS CAMPURAN ASPAL PENETRASI 60/70 TEHADAP VARIASI LAMA WAKTU PERENDAMAN - Fadhil, Ammar; Khairunnisa, Hanyta (Jurnal Sains Riset, 2024)
ABSTRACTThe utilization of plastic waste can be done by using it as an additive in asphalt concrete wearing course (AC-WC) mixtures. Incorporating plastic waste into road construction serves two purposes: reducing plastic waste and enhancing road quality. This research aims to determine the durability value when 7% PET plastic is immersed at 60°C for 0.5 hours, 24 hours, 36 hours, 48 hours, and 72 hours in a 60/70 penetration asphalt mixture. This study was conducted by adding PET pieces in a dry condition. The Optimal Asphalt Content (OAC) obtained from the test specimen was 6.29% (Marwati et al., 2021). From the Marshall test results without PET, the 24-hour durability value was 94.13%, and with the addition of 7% PET, the durability value at 24 hours increased to 96.16% and at 36 hours to 91.57%, meeting the specification of ≥ 90%, while at 48 hours it was 83,31%, and at 72 hours it was 80,70% which did not meet the requirements. The stability value increased due to the addition of PET in the asphalt mixture compared to the asphalt mixture without PET. The addition of 7% PET still met the requirements for a 36-hour immersion time in water with a stability value of 1094.13 kg, and Marshall parameters such as VIM 4.83%, VFA 79.41%, VMA 23.17%, MQ 288.57 kg/mm, and flow 3.80 mm met the specifications of Bina Marga 2020.